Response Surface and Kinetic Modeling of Dimethyl Sulfide Oxidation – On the Origin of Dimethyl Sulfoxide in Malt. (2nd January 2018) - Baldus, M.; Tsushima, S.; Xi, D.; Majetschak, S.; Methner, F.-J.
ABSTRACT: Dimethyl sulfide (DMS) contributes significantly to beer aroma. Malt contains considerable amounts of its oxidized form dimethyl sulfoxide (DMSO), the precursor of DMS during fermentation. Yet, detailed information regarding mechanisms of DMSO formation in malt is limited. Recently, hydrogen peroxide was suggested as a potential DMS oxidant in malt. The aim of this study was to characterize the reaction of hydrogen peroxide and DMS in buffered model solutions. Initially, hydrogen peroxide was identified in green malt using leuco crystal violet and horseradish peroxidase. Based on these findings the reaction of DMS with H2 O2 was investigated in buffered model solutions at varying temperatures and pH using response surface modeling (RSM). Significant amounts of DMSO were formed by H2 O2 mediated oxidation of DMS (∼0–41%), which was determined by temperature and hydrogen peroxide concentration ( P ≤ 0.003). The effect of the pH was insignificant ( P ≥ 0.4). Kinetics of DMS oxidation by H2 O2 (DMS:H2 O2 = 1:3) at 95°C followed a pseudo first order mechanism (k = 0.0041 min −1 ). Molecular oxygen was not capable of oxidizing DMS, whereas hydroxyl radical mediated DMS oxidation was faster than DMS oxidation aroused by H2 O2 . Potential reaction mechanisms and their relevance in DMS oxidation are discussed as a first approach to minimize DMSO levels in malt.